Cellular clones ; Waging peace in Sagada ; Madama Butterfly [videorecording] - Lazaro, Cheche; Santos, Owen. (Quezon City Probe Productions, 1994)
The technological disadvantages of cellular phones cloners or duplicators of cellular phone lines have victimized cell phone users, making them pay exorbitant fees for calls they never made. Deals with Sagadans declaration of their area as a peace zone. A group of artists want to change opera.
Cellular clones (16 min.) -- Peace in Sagada (16 min.) -- Mada Butterfly (18 min.)
VHS.
Reporter, Luchi Cruz-Valdes.
Keywords: Cellular radio -- Philippines; Church and social problems -- Philippines -- Sagada (Mt. Province); Opera producers and directors -- Philippines -- Interviews; Musicals -- Philippines